THE ROLE OF HUMAN CAPITAL IN MODERATING THE INFLUENCE OF MSME INVESTMENT AND GROSS FIXED CAPITAL FORMATION ON INCLUSIVE ECONOMIC GROWTH IN INDONESIA - Yusnidar Yusnidar; Srinita Srinita; Muhammad Abrar (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study investigates the short-run effects of Micro, Small, and Medium Enterprise (MSME) investment and Gross Fixed Capital Formation (GFCF) on inclusive economic growth in Indonesia, with human capital included as a moderating variable. Using annual time-series data from 1990 to 2024 sourced from the World Bank, the analysis applies Moderated Regression Analysis (MRA) to evaluate the interaction between investment and human capital. The empirical findings show that MSME investment and human capital exert strong and significant positive influences on inclusive growth, while GFCF demonstrates a positive but relatively modest direct impact. Furthermore, human capital significantly enhances the effects of both MSME investment and GFCF, emphasizing its role as a catalyst in improving investment productivity and inclusiveness. This study provides updated empirical evidence on Indonesia’s investment–growth nexus by applying an interaction-based MRA framework to long-term data, highlighting the strategic importance of integrating human capital development within investment-driven growth policies.